The Correlation of Knowledge and Attitude of Pregnant Women and The Compliance of Birth Planning and Complication Prevention Program (P4K) in Ringinpitu Kecamatan Pelemahan Kabupaten Kediri - Ratna Feti Wulandari; Ratih Kusuma Wardhani; Maria Ulfa (STIKes Patria Husada Blitar, 2022)
Maternal mortality rate (MMR) is an indicator of the assessment of maternal health programs and the degree of public health. The program launched by the government in an effort to reduce MMR was the Maternity Planning and Complications Prevention Program (P4K) which aimed to monitor pregnancies into safe and secure deliveries. In order to accomplish the importance of planning for delivery and preventing the complications, it is necessary to conduct research on the knowledge and attitudes of pregnant women and the compliance in implementing P4K. The purpose of the study was to analyze the correlation of knowledge and attitudes of pregnant women and the compliance of birth planning and complication prevention program (P4K). this research used a cross sectional design with an analytical survey. The research was conducted in Ringinpitu Village from March to October 2020. The population was pregnant women in Ringinpitu Village. The sampling technique used simple random sampling with the total sample of 26 people. The data collection used primary data. The instrument used a questionnaire. The data was processed by Spearmen rank test with correlation analysis. Based on the results of the research, it was found that the knowledge of pregnant women about P4K was in the fair category (42.3%). The attitude of pregnant women about P4K showed a positive attitude (65.4%). The compliance of pregnant women in implementing P4K was (38.5%). There was a correlation between knowledge of pregnant women and P4K compliance (p value = 0.0000) p <0.05 correlation coefficient r = 0.671 which meant there was a strong level of correlation and there was a correlation between the attitude of pregnant women and compliance to P4K (p value = 0.001) p < 0.05 correlation coefficient r = 0.604. Compliance with P4K will greatly help the government in reducing maternal mortality and infant mortality.